From the Palmer Raids to the Patriot Act a history of the fight for free speech in America - Finan, Christopher M., 1953-; ebrary, Inc. (Boston, Mass. : Beacon Press, 2007)
Presents a comprehensive history of the evolution of free speech in America over the last century.
Ground zero -- Mob rule, 1921-1930 -- Banned in Boston -- The court takes a hand -- The second Red scare -- The fight for artistic freedom, 1945-1966 -- Let the sunshine in -- The counterattack, 1970-2002 -- 9/11.
Includes bibliographical references (p. 310-325) and index.
Electronic reproduction.
Keywords: Freedom of speech -- United States -- History; Freedom of speech -- United States -- History; Electronic books